Dynamics of Early Intervention Specialists Needs in the Context of Their Emotional State During the War in Ukraine - Kukuruza, Hanna; Bliznyuk, Olena; Tsylyuryk, Serhiy (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2024)
The aim of the work was to determine the features of the dynamics of early intervention specialists needs in the context of their emotional state during the war in Ukraine. The following research methods and techniques were used: the questionnaire method to assess the motivational and needs sphere of early intervention specialists, assessment of satisfaction of personal  needs , emotional-volitional and work spheres of life of RW specialists and the methodology of K. Izard's "Differential Emotion Scale" for analyzing the affective components of activity regulation, reflecting the peculiarities of the subject's motivational attitudes. The study was conducted in August - September 2023. 85 specialists from Kharkiv, Zakarpattia, Odessa, Lviv, Donetsk, Luhansk regions and Vinnytsia city, who work in early intervention, participated in the study. Results. The hierarchy of needs of RW specialists after the start of large-scale Russian aggression was determined. In the first place - obtaining new knowledge about supporting families and children during the war, knowledge about trauma and working with it, then - communication with colleagues, financial and material needs, the need for emotional support to prevent emotional burnout, etc. The positive dynamics of satisfaction of needs in the professional sphere of RW specialists were determined (improved since the beginning of the war): the need for awareness about working with families in a war situation, the ability to integrate new ideas into daily practice, the ability to act creatively and produce new ideas. The greatest positive dynamics in relation to the personal sphere were recorded in relation to the level of energy and activity, the ability to regulate own emotions, satisfaction with ordinary affairs, and the ability to make decisions. The negative dynamics of needs in the personal sphere are associated with understanding the future, a sense of security, and the ability to concentrate.